Proceedings of the 25th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval 2002
DOI: 10.1145/564376.564408
|View full text |Cite
|
Sign up to set email alerts
|

Cross-lingual relevance models

Abstract: We propose a formal model of Cross-Language Information Retrieval that does not rely on either query translation or document translation. Our approach leverages recent advances in language modeling to directly estimate an accurate topic model in the target language, starting with a query in the source language. The model integrates popular techniques of disambiguation and query expansion in a unified formal framework. We describe how the topic model can be estimated with either a parallel corpus or a dictionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(64 citation statements)
references
References 13 publications
0
64
0
Order By: Relevance
“…The query likelihood method and the KL-divergence method have been shown to perform well for a variety of retrieval tasks, including ad-hoc retrieval (Ponte and Croft 1998;Zhai and Lafferty 2001b;Lafferty and Zhai 2001), cross-lingual information retrieval (Xu et al 2001;Lavrenko et al 2002), distributed information retrieval (Xu and Croft 1999;Si et al 2002), structured document retrieval (Ogilvie and Callan 2003), personalized and context-sensitive search (Shen et al 2005;Tan et al 2006), modeling redundancy (Zhang et al 2002), predicting query difficulty (Cronen-Townsend et al 2002), expert finding (Balog et al 2006;Fang and Zhai 2007), passage retrieval (Liu and Croft 2002;Lv and Zhai 2009), subtopic retrieval , etc.…”
Section: Language Modeling Retrieval Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The query likelihood method and the KL-divergence method have been shown to perform well for a variety of retrieval tasks, including ad-hoc retrieval (Ponte and Croft 1998;Zhai and Lafferty 2001b;Lafferty and Zhai 2001), cross-lingual information retrieval (Xu et al 2001;Lavrenko et al 2002), distributed information retrieval (Xu and Croft 1999;Si et al 2002), structured document retrieval (Ogilvie and Callan 2003), personalized and context-sensitive search (Shen et al 2005;Tan et al 2006), modeling redundancy (Zhang et al 2002), predicting query difficulty (Cronen-Townsend et al 2002), expert finding (Balog et al 2006;Fang and Zhai 2007), passage retrieval (Liu and Croft 2002;Lv and Zhai 2009), subtopic retrieval , etc.…”
Section: Language Modeling Retrieval Modelsmentioning
confidence: 99%
“…The language modeling approach to information retrieval (Ponte and Croft 1998) has recently enjoyed much success for many different retrieval tasks (Ponte and Croft 1998;Xu and Croft 1999;Zhai and Lafferty 2001b;Lafferty and Zhai 2001;Xu et al 2001;Lavrenko et al 2002;Si et al 2002;Zhang et al 2002;Cronen-Townsend et al 2002;Liu and Croft 2002;Zhai et al 2003;Ogilvie and Callan 2003;Shen et al 2005;Tan et al 2006;Balog et al 2006;Fang and Zhai 2007;Zhai 2008;Lv and Zhai 2009;Tsagkias et al 2011). In the language modeling approach, we assume that a query is a sample drawn from a language model: given a query Q and a document D, we compute the likelihood of ''generating'' query Q with a document language model estimated based on document D. We can then rank documents based on the likelihood of generating the query, i.e., query likelihood.…”
Section: Introductionmentioning
confidence: 99%
“…So CLIR is more complex than monolingual IR. At present, query translation has become the most popular technique for CLIR [6]. Through query translation, CLIR task can be converted into monolingual IR task.…”
Section: English-chinese Query Translationmentioning
confidence: 99%
“…Conventionally CLIR approaches [4,7,8,12,21] have focused mainly on incorporating dictionaries and domain-specific bilingual corpora for query translation [6,10,18]. The general assumption of such approaches is that the incorrect translation of a few query terms in a query is tolerable and can be remedied via query expansion in the process of document retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous Web search engine log analyses revealed that the average query length for a Web search was about 2.3 words in English [17] and 3.18 characters in Chinese [13]. Conventional CLIR approaches [8,21] that are based on domainspecific corpora might not be applicable to dealing with the translation of short queries with unknown terms. First, sufficiently large bilingual corpora for certain subject domains and language pairs are not always available.…”
Section: Introductionmentioning
confidence: 99%